Local Community and Its Existence: The Environmental Wisdom of Kasepuhan Community at Kampong Cengkuk, Sukabumi District, West Java - Ary Sulistyo (Sosioglobal, 2019)
The research focused on the eternality of environmental preservation of indigenous Sunda Village of Kasepuhan Ciptagelar at Southern Halimun Mountain, Sukabumi District, West Java. The local community still exist with living heritage of Sundaness tradition and culture as well as rural tourism. The study associated with the depreciation of land and population growth. Socio-culture approach on this research has focused into environmental wisdom values that occupied the forest land. The result showed that Kasepuhan indigenous tradition is still practicing by community that protected the forestland at the south of the settlement only for their subsistence. Social-culture changes were occurring in the community with no agricultural activities in the forest (outer islands agriculture), but farmed in rice field activities (wet rice cultivation). Reduction in process and ceremonial activities also happened. More profane activities were developing economic crops in kebun-talun. The spatial pattern in environmental aspect was still have position; mountains-settlement-rivers; the main village of Kasepuhan—and the compose of several cluster villages. Indigenous villages that were geographically higher usually have more stricted tradition than the lower one.